Case Report: Hyperplastic Callus of the Femur Mimicking Osteosarcoma in Osteogenesis Imperfecta Type V - Deng, Ying; Huo, Yanan; Li, Jinfeng (Frontiers in Endocrinology, 2021)
Background: Osteogenesis imperfecta (OI) type V is a rare form of OI which is often characterized by hyperplastic callus. Misdiagnosis is a possibility due to its rarity and because patients involved are mostly in adolescence, a predisposing age for osteosarcoma. Here, we report this case and aim to improve understanding of patients with OI type V and avoid misdiagnosis. Case presentation: A male, 14-year-old patient was admitted to Jiangxi Provincial People's Hospital affiliated to Nanchang University in Aug. 2020 due to repeated fractures for more than 11 years and swelling in his right leg for more than 4 years. The patient was diagnosed with OI in 2014 due to repeated fracture and was treated with bisphosphonates. The swelling was accompanied by huge callus formation. Prior to admission to our hospital in 2016 osteosarcoma was suspected by imaging and pathology, and amputation was recommended. OI-V was confirmed after more than four years of follow-up and genetic diagnosis, and the affected limb was preserved. Conclusion: The history of OI and lack of rapid progression suggested OI-V with a hyperplastic callus. Combined with genetic testing, the diagnosis was OI-V. Although the patient was at a predisposing age for osteosarcoma, diagnosis and treatment should be based on the medical history of the patient, imaging, pathology and genetic testing, and sometimes even time-consuming retrospective observation.